2004
DOI: 10.1128/aem.70.7.3845-3854.2004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heterologous Expression of Escherichia coli UDP-Glucose Pyrophosphorylase on Trehalose and Glycogen Synthesis in Corynebacterium glutamicum

Abstract: Trehalose is a disaccharide with a wide range of applications in the food industry. We recently proposed a strategy for trehalose production based on improved strains of the gram-positive bacterium Corynebacterium glutamicum. This microorganism synthesizes trehalose through two major pathways, OtsBA and TreYZ, by using UDP-glucose and ADP-glucose, respectively, as the glucosyl donors. In this paper we describe improvement of the UDP-glucose supply through heterologous expression in C. glutamicum of the UDP-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
3
26
1
Order By: Relevance
“…Tryptone soybean broth (TSB) medium was used for the cultivation of C. glutamicum. The culture media defined for C. glutamicum for shake flask experiments (DMCG I) and for batch bioreactor cultivation experiments (DMCG II) were prepared as described previously (7,22,23). Antibiotics were added to obtain final concentrations of 50 g of ampicillin and 20 g of chloramphenicol/ ml, while IPTG (isopropyl-␤-D-thiogalactopyranoside) was added to obtain a final concentration of 1.0 mM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tryptone soybean broth (TSB) medium was used for the cultivation of C. glutamicum. The culture media defined for C. glutamicum for shake flask experiments (DMCG I) and for batch bioreactor cultivation experiments (DMCG II) were prepared as described previously (7,22,23). Antibiotics were added to obtain final concentrations of 50 g of ampicillin and 20 g of chloramphenicol/ ml, while IPTG (isopropyl-␤-D-thiogalactopyranoside) was added to obtain a final concentration of 1.0 mM.…”
Section: Methodsmentioning
confidence: 99%
“…Increased glycogen supplied during the single expression of galU suggests that the higher trehalose was synthesized through the TreYZ pathway (23). Rather than trying to establish the interrelationship in the two pathways' mechanisms, the aim of the present study was to seek higher trehalose production, making use of the simultaneous expression of C. glutamicum treY and treZ genes in the TreYZ pathway and the E. coli galU gene (11,23). …”
mentioning
confidence: 99%
“…Previous studies have revealed a link between glycogen and trehalose synthesis in C. glutamicum, suggesting a role of glycogen metabolism for fast adaptation to hyperosmotic growth conditions (Padilla et al, 2004;Seibold et al, 2007;Tzvetkov et al, 2003;Wolf et al, 2003). We therefore examined the effects of salt addition in the exponentialgrowth phase on growth, substrate consumption, glycogen level and intracellular trehalose formation of C. glutamicum WT, using minimal medium with 1.5 % glucose as a carbon source.…”
Section: Role Of the Debranching Enzyme Glgx For Growth Under Hyperosmentioning
confidence: 99%
“…before complete consumption of the sugar substrate (Seibold et al, 2007). Therefore, it seems unlikely that glycogen in this organism serves as a long-term carbon storage compound, and in fact, glycogen metabolism in C. glutamicum has previously been suggested to be important for trehalose synthesis (Padilla et al, 2004;Seibold et al, 2007;Tzvetkov et al, 2003;Wolf et al, 2003). It has been shown that linear maltodextrins (formed as intermediates during glycogen synthesis and degradation) serve as substrates for the two-step trehalose biosynthetic pathway via maltooligosyltrehalose synthase (TreY) and maltooligosyltrehalose trehalohydrolase (TreZ) (Carpinelli et al, 2006;De Smet et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Padilla et al (2004) increased the UDP glucose supply and consequently the levels of accumulated trehalose by expressing the E. coli galU gene in Corynebacterium glutamicum. In our study, the expression of both the galE(3) and galE(25) genes in the osmosensitive strain E. coli MKH13 resulted in a statistically significant increased salt (NaCl and KCl) tolerance phenotype (Figures 2b and c).…”
Section: Discussionmentioning
confidence: 99%